2013
DOI: 10.1016/j.jacc.2013.07.057
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Subpopulations Are Essential for Infarct Repair With and Without Stem Cell Therapy

Abstract: Some of the protective effects of MSCs on infarct repair are mediated by macrophages, which are essential for early healing and repair. Thus, targeting macrophages could be a novel strategy to improve infarct healing and repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
208
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(227 citation statements)
references
References 38 publications
16
208
2
1
Order By: Relevance
“…In fact, previous studies have reported that M2 macrophages are necessary for promoting angiogenesis following MI [35,36]. Moreover, macrophages are clearly involved in the cardioprotective effect of transplanted BMSCs in mouse MI [37]. Given that transplanted W8B2 1 CRSCs did not show appreciable differentiation into cardiovascular cell types in the myocardium, direct differentiation of W8B2 1 CRSCs into a functional unit of the heart is unlikely to account for cardioprotection by this cell treatment.…”
Section: Discussionmentioning
confidence: 86%
“…In fact, previous studies have reported that M2 macrophages are necessary for promoting angiogenesis following MI [35,36]. Moreover, macrophages are clearly involved in the cardioprotective effect of transplanted BMSCs in mouse MI [37]. Given that transplanted W8B2 1 CRSCs did not show appreciable differentiation into cardiovascular cell types in the myocardium, direct differentiation of W8B2 1 CRSCs into a functional unit of the heart is unlikely to account for cardioprotection by this cell treatment.…”
Section: Discussionmentioning
confidence: 86%
“…Both reports propose that modulation of epicardial paracrine environment is potentially key for the observed enhanced myocardial repair (Huang et al, 2012;Zhou et al, 2011), underscoring the potentially important role of cTMs and exogenous macrophages in regulating the post-MI inflammatory milieu and tissue repair. The finding that macrophage signalling, particularly from M2-like macrophages, enhances MSC survival, engraftment and potentially also differentiation (Ben-Mordechai et al, 2013;Freytes et al, 2013), suggests that the role of macrophage signalling may be also important for the regulation of epicardial progenitor cells to repair the damaged myocardium.…”
Section: Macrophages and Regulation Of Epicardial Progenitorsmentioning
confidence: 99%
“…A relatively high amount of two pro-inflammatory mediators, MCP-1/CCL2 and IL-1b, are also expressed by MGs on MSC coculture. We can only speculate that due to the fact that mononuclear phagocytes with various phenotypic polarization are crucial for tissue repair and regeneration [47,48], the MCP-1/CCL2-induced microglia accumulation at the site of tissue injury or inflammation could have a beneficial effect on the repair process. On the other hand, the IL-1b secretion by MGs in the presence of stem cells is consistent with an earlier report [35] and could be explained by two facts.…”
Section: Microglia Activation and Effector Functionsmentioning
confidence: 99%